2007
DOI: 10.1071/mf06150
|View full text |Cite
|
Sign up to set email alerts
|

A decline in the abundance and condition of a native bivalve associated with Caulerpa taxifolia invasion

Abstract: Caulerpa taxifolia is a fast-spreading invasive seaweed that threatens biodiversity in temperate Australian estuaries. To date, little is known about its effects on infauna. In the present study, we describe variation in demographic and life-history traits of the abundant infaunal bivalve, Anadara trapezia, in C. taxifolia and uninvaded habitats (seagrass and unvegetated sediments) at multiple sites across three estuaries in south-eastern New South Wales. Densities of A. trapezia were always lower in C. taxifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 53 publications
1
58
0
Order By: Relevance
“…Research into C. taxifolia has focused largely on its range expansion (e.g. Meinesz et al 2001) and effects of the live alga on local seagrass populations (Ceccherelli & Cinelli 1997, Ceccherelli & Sechi 2002, Holmer et al 2009), epi-and in-fauna (Gollan & Wright 2006, Wright et al 2007, McKinnon et al 2009) and fish assemblages (York et al 2006). Also, C. taxifolia also has the potential to markedly alter detrital pools.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Research into C. taxifolia has focused largely on its range expansion (e.g. Meinesz et al 2001) and effects of the live alga on local seagrass populations (Ceccherelli & Cinelli 1997, Ceccherelli & Sechi 2002, Holmer et al 2009), epi-and in-fauna (Gollan & Wright 2006, Wright et al 2007, McKinnon et al 2009) and fish assemblages (York et al 2006). Also, C. taxifolia also has the potential to markedly alter detrital pools.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…A number of studies have identified changes in ecological communities such as seagrass (DeVille and Verlaque 1995;Ceccherelli and Sechi 2002), fish (York et al 2006), bivalves (Wright et al 2007), and soft-sediment macroinvertebrates (McKinnon et al 2009) following C. taxifolia invasion. Water column and sediment properties and physical processes are also modified by C. taxifolia colonization.…”
mentioning
confidence: 99%
“…Caulerpa was first discovered in Lake Conjola in 2000 (Creese et al 2004) and within eight years spread to cover .25% of the benthos, including nearly all of the benthos in shallow water (0.25-3 m; State of New South Wales, Department of Primary Industries 2005). At our study site, Anadara occurs in increasingly rare patches of unvegetated sediments and in Caulerpa-invaded sediments, although at lower densities (Wright et al 2007). Native seagrasses are present in Lake Conjola but they are sparse and restricted to shallow areas fringing the bay.…”
Section: Species and Study Locationmentioning
confidence: 97%
“…Recruitment of Anadara is significantly greater to Caulerpa habitat (Gribben and Wright 2006b), perhaps due to enhanced capture and retention of particles resulting from its reduction of water velocities (Gribben et al 2009b). However, ultimately Anadara populations are very negatively affected by Caulerpa, with the higher recruit densities inside Caulerpa driven to equally low levels within a year (Gribben et al 2009b) and adult densities in Caulerpa as low as one-fifth of those in unvegetated areas (Wright et al 2007). However, the manner in which Anadara populations are reduced is unclear.…”
Section: Study Systemmentioning
confidence: 99%
See 1 more Smart Citation